Actuation distribution and workspace analysis of a novel 3(3RRlS) metamorphic serial-parallel manipulator for grasping space non-cooperative targets. (September 2019) - Zhao, Chong; Guo, Hongwei; Liu, Rongqiang; Deng, Zongquan; Li, Bing; Tian, Jin
Abstract: Capturing non-cooperative targets in space is a cutting-edge technology in the aerospace field. In this study, a novel n (3RRlS) metamorphic serial-parallel manipulator (MSPM) with multiple working conditions is proposed, which can serve as the fingers of a large-scale reconfigurable space multifingered hand (LSRSMFH). First, a limb combination coding method is proposed to describe the topological graph and determine the isomorphism of the n (3RRlS) MSPM. Subsequently, the topological graphs and the limb combination codes (LCCs) of the 1(3RRlS) MSPM, 2(3RRlS) MSPM and 3(3RRlS) MSPM are further analyzed, and the isomorphism of all the actuation distribution configurations (ADCs) and metamorphic configuration states (MCSs) is determined. Second, a two-actuator method is applied for the n (3RRlS) MSPM, and the workspaces of all MCSs of all ADCs of the 1(3RRlS) MSPM, 2(3RRlS) MSPM and 3(3RRlS) MSPM are analyzed using a transformation method. The results show that the n (3RRlS) MSPM can realize their respective functions of the LSRSMFH under three working conditions with the minimum number of actuators, which can reduce the number of actuators and the weight of the LSRSMFH and can gain benefits in multitask adaptability, simplified control, precision and rigidity improvement, energy saving and risk reduction.